Electrode and preparation method thereof, battery and electric equipment

By using a protective layer of lithium alloy and acid polymer on the lithium metal electrode, the lithium dendrites problem caused by uneven lithium ion deposition is solved, and the stability of the electrode and the battery life are improved.

CN119133359APending Publication Date: 2024-12-13BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411048914.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the cycle charging and discharging process, lithium dendrites are formed due to uneven deposition of lithium ions, piercing the separator and consuming the electrolyte, affecting the cycle life of the battery.

Method used

A protective layer including lithium alloy and acid polymer is used to form a stable protective layer through covalent connection, reducing the lithium ion deposition overpotential and preventing the formation of lithium dendrites and electrode oxidation.

Benefits of technology

Effectively isolate air, prevents active materials from oxidizing, extends electrode life, uniforms lithium ion current, prevents lithium dendrites from punctured by the separator, reduces battery polarization, and improves battery safety performance and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133359A_ABST
    Figure CN119133359A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode and a preparation method thereof, a battery and electric equipment. The electrode includes: an active material layer; the protective layer is positioned on one side of the active material layer, and the protective layer comprises a polymer and an alloy; the alloy comprises a lithium alloy; the polymer includes an acidic polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode technology, and more specifically, to an electrode and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In the related technology, lithium metal can be used as the negative electrode material of the battery. During the cyclic charging and discharging process, lithium metal will produce lithium dendrites due to the uneven deposition of lithium ions. The lithium dendrites will not only pierce the separator between the positive and negative electrodes, causing a short circuit in the battery, but also consume a large amount of electrolyte during the cyclic charging and discharging process, affecting the cycle life of the battery.

[0003] Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention

[0004] An object of the present invention is to provide a new technical solution for electrodes.

[0005] According to a first aspect of the present invention, an electrode is provided. The electrode comprises:

[0006] an active material layer;

[0007] A protective layer, the protective layer is located on one side of the active material layer, and the protective layer comprises a polymer and an alloy;

[0008] The alloy comprises a lithium alloy;

[0009] The polymer includes an acidic polymer.

[0010] Optionally, the acidic polymer includes at least one of Compound 1 and Compound 2, and the general formulas of Compound 1 and Compound 2 are respectively:

[0011]

[0012] wherein R1 is -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2(CHCH3)CH2-, -PhCH2CH2-, -PhCH2CH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2CH2-, -CH2COCH2-, -CH2OCH2-, -CH2CH2OCH2-, -CH2CH2OCH2CH2-, or -CH2CH2OCH2CH2OCH2CH2-;

[0013] R2 is -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2(CHCH3)CH2-, -PhCH2CH2-, -PhCH2CH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2CH2-, -CH2COCH2-, -CH2OCH2-, -CH2CH2OCH2-, -CH2CH2OCH2CH2-, or -CH2CH2OCH2CH2OCH2CH2-;

[0014] X1 is -COOH, -(CH2) d COOH, -SO3H, -(CH2) d SO3H or -CF3COOH, d is a natural number;

[0015] X2 is -NHCOCF3, -NHSO2CF3 or -CF3SO2NHSO2CF3;

[0016] m and n are both natural numbers, n / (m+n)=0.01-0.99, m / (m+n)=0.01-0.99;

[0017] a and b are both natural numbers, a / (a+b)=0.01-0.99, b / (a+b)=0.01-0.99.

[0018] Optionally, the metal in the alloy is covalently bonded to the acidic polymer.

[0019] Optionally, the active material layer includes at least one of lithium metal, lithium alloy and silicon-containing electrode material.

[0020] Optionally, the lithium alloy includes at least one of lithium boron alloy, lithium magnesium alloy, lithium aluminum alloy, lithium tin alloy, lithium germanium alloy, lithium gallium alloy, lithium indium alloy, lithium antimony alloy, lithium indium alloy, lithium zinc alloy, lithium lead alloy, lithium bismuth alloy, lithium gold alloy, and lithium silver alloy.

[0021] Optionally, the silicon-containing electrode material includes at least one of silicon element, silicon monoxide, a silicon-carbon composite material, and a silicon-iron composite material.

[0022] According to a second aspect of the present application, a method for preparing an electrode is provided. The method comprises:

[0023] The slurry containing the polymer and the alloy is applied to one side of the active material layer and dried to obtain the electrode.

[0024] Optionally, the lithium alloy is obtained by reacting at least a metal carbonate and an organic lithium salt.

[0025] Optionally, the metal carbonate includes at least one of gold carbonate, silver carbonate, magnesium carbonate, tin carbonate and zinc carbonate.

[0026] Optionally, the organic lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium hexafluorophosphate.

[0027] Optionally, the method for preparing the slurry comprises:

[0028] Mixing the polymer, the metal carbonate and an organic solvent to obtain a first solution;

[0029] Drying the first solution to obtain a solid;

[0030] The solid matter is dissolved in a solution containing the organic lithium salt to obtain the slurry.

[0031] Optionally, the organic solvent includes at least one of tetrahydrofuran, N,N'-dimethylformamide, N,N'-dimethylacetamide, dioxane, ethanol, toluene and xylene.

[0032] Optionally, the organic solvent further includes at least one of hydrochloric acid, sulfuric acid, trifluoroacetic acid, acetic acid, phosphoric acid, methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, oxalic acid, and succinic acid.

[0033] Optionally, the solution containing the organic lithium salt contains acetonitrile.

[0034] Optionally, the mass ratio of the polymer, the organic lithium salt and the acetonitrile is (0.5-1.5):(0.6-0.9):(0.5-1.5).

[0035] According to a third aspect of the present application, a battery is provided, which includes the electrode described in the present application or an electrode prepared by the method for preparing the electrode described in the present application.

[0036] According to a fourth aspect of the present application, an electrical device is provided, which includes the battery described in the present application.

[0037] In the embodiments of the present application, the protective layer can effectively protect the active material layer and can effectively isolate the air to prevent the active material layer from oxidation. The protective layer can also prevent the active electrode layer from reacting with the electrolyte, thereby extending the service life of the electrode. Lithium alloys can reduce the overpotential of lithium ion deposition, thereby achieving the effect of reducing battery polarization. Lithium alloys can also make the lithium ion current uniform, preventing lithium ions from concentratedly depositing to form lithium dendrites, thereby effectively preventing lithium dendrites from piercing the battery's diaphragm.

[0038] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0040] Figure 1 is a cross-sectional view of a negative electrode sheet according to an embodiment of the present application.

[0041] Figure 2 yes Figure 1 A partial enlarged view of point A in the middle.

[0042] Figure 3 It is a curve showing the change of the charging and discharging voltage of the battery of the embodiment of the present application and comparative examples 1 and 2 over time.

[0043] Description of reference numerals:

[0044] 10. Current collector; 20. Active material layer; 30. Alloy layer; 40. Polymer layer; 41. Metal-grafted polymer; 42. Lithium ion current. DETAILED DESCRIPTION

[0045] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0046] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0047] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0048] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0049] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0050] According to a first embodiment of the present application, an electrode is provided. Figure 1 to Figure 2 As shown, the electrode comprises:

[0051] Active material layer 20;

[0052] A protective layer, the protective layer is located on one side of the active material layer, and the protective layer comprises a polymer and an alloy;

[0053] The alloy comprises a lithium alloy;

[0054] The polymer includes an acidic polymer.

[0055] Specifically, the active material layer 20 includes at least one of lithium metal, lithium alloy and silicon-containing electrode material. The above-mentioned active material layer 20 is a negative electrode active material. The electrode is a negative electrode. Optionally, the lithium alloy includes at least one of lithium boron alloy, lithium magnesium alloy, lithium aluminum alloy, lithium tin alloy, lithium germanium alloy, lithium gallium alloy, lithium indium alloy, lithium antimony alloy, lithium indium alloy, lithium zinc alloy, lithium lead alloy, and lithium bismuth alloy. The silicon-containing electrode material includes at least one of silicon element, silicon oxide, silicon carbon composite material, and silicon iron composite material. The active material layer 20 is attached to the current collector 10. The material of the current collector 10 is metal. For example, the current collector 10 is a sheet of copper, aluminum, nickel, lithium, etc. Figure 1 A negative electrode sheet is shown. An active material layer 20 and a protective layer are sequentially attached to the surface of a current collector 10 of the negative electrode sheet.

[0056] Acidic polymer refers to a polymer compound having an acidic functional group. The acidic functional group may be, but is not limited to, a carboxyl group, a sulfonic acid group, a phosphoric acid group, etc. The acidic functional group makes the acidic polymer acidic.

[0057] In the embodiment of the present application, the protective layer can effectively protect the active material layer 20, and can effectively isolate the air to prevent the active material layer 20 from oxidation. The protective layer can also prevent the active electrode layer from reacting with the electrolyte, thereby extending the service life of the electrode. Lithium alloys can reduce the deposition overpotential of lithium ions (deposition overpotential refers to the change in electrode potential when a substance is reduced or oxidized and deposited on the electrode surface in an electrochemical reaction), thereby achieving the effect of reducing battery polarization. Lithium alloys can also make the lithium ion current 42 uniform, preventing lithium ions from concentratedly depositing to form lithium dendrites, thereby effectively preventing lithium dendrites from piercing the battery's diaphragm.

[0058] Preferably, after volume separation and formation, the acidic polymer forms a polymer layer 40, and the lithium alloy in the protective layer forms an alloy layer 30. The polymer layer 40 can effectively protect the alloy layer 30, and can effectively isolate the air to prevent the active electrode layer 20 from oxidation. The polymer layer 40 can also prevent the active electrode layer from reacting with the electrolyte, thereby extending the service life of the battery. The alloy layer 30 can reduce the overpotential of lithium ion deposition, thereby achieving the effect of reducing battery polarization. The alloy layer 30 can also make the lithium ion current 42 uniform, prevent lithium ions from concentratedly depositing to form lithium dendrites, thereby effectively preventing lithium dendrites from piercing the battery's diaphragm. Due to the high strength of the alloy layer 30, the volume expansion of the electrode can be effectively suppressed.

[0059] In other embodiments, the acidic polymer and the lithium alloy do not form a layered structure, and the two are evenly dispersed in the protective layer. The protective layer can also prevent the active electrode layer 20 from being oxidized, reduce the overpotential of lithium ion deposition, prevent the formation of lithium dendrites, and inhibit the volume expansion of the electrode.

[0060] In one example, the acidic polymer includes at least one of compound 1 and compound 2, and the general formulas of compound 1 and compound 2 are respectively:

[0061]

[0062] wherein R1 is -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2(CHCH3)CH2-, -PhCH2CH2-, -PhCH2CH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2CH2-, -CH2COCH2-, -CH2OCH2-, -CH2CH2OCH2-, -CH2CH2OCH2CH2-, or -CH2CH2OCH2CH2OCH2CH2-;

[0063] R2 is -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2(CHCH3)CH2-, -PhCH2CH2-, -PhCH2CH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2CH2-, -CH2COCH2-, -CH2OCH2-, -CH2CH2OCH2-, -CH2CH2OCH2CH2-, or -CH2CH2OCH2CH2OCH2CH2-;

[0064] X1 is -COOH, -(CH2) d COOH, -SO3H, -(CH2) d SO3H or -CF3COOH, d is a natural number;

[0065] X2 is -NHCOCF3, -NHSO2CF3 or -CF3SO2NHSO2CF3;

[0066] m and n are both natural numbers, n / (m+n)=0.01-0.99, m / (m+n)=0.01-0.99;

[0067] a and b are both natural numbers, a / (a+b)=0.01-0.99, b / (a+b)=0.01-0.99.

[0068] In this example, the two compounds can be covalently bonded to the metal in the lithium alloy of the protective layer and have a strong bonding force with the active material layer 20, thereby improving the durability of the electrode.

[0069] Optionally, m is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9; n is 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1. a is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9; b is 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1. Within the above ranges, both compounds can be covalently bonded to the metal in the lithium alloy.

[0070] Preferably, the lithium alloy in the protective layer includes at least one of lithium gold alloy, lithium silver alloy, lithium magnesium alloy, lithium tin alloy and lithium zinc alloy. The deposition overpotential of the above lithium alloy is lower than that of other lithium alloys, which makes it easier to form the protective layer.

[0071] In this example, the alloy has high structural strength and can effectively suppress the volume expansion of the electrode sheet during the cyclic charge and discharge process.

[0072] In one example, the metal in the alloy is covalently bonded to the acidic polymer.

[0073] In this example, the acidic polymer can be covalently bonded to the lithium in the alloy layer 30, ie, grafted, which makes the connection strength between the alloy layer 30 and the polymer layer 40 strong, further improving the durability of the electrode.

[0074] In one example, the active material layer 20 includes at least one of lithium metal, lithium alloy, and silicon-containing electrode material.

[0075] The above materials can all be used as negative electrode active materials. A protective layer is formed on one side of the above materials. The protective layer is firmly bonded to the active material layer.

[0076] In one example, the lithium alloy includes at least one of lithium boron alloy, lithium magnesium alloy, lithium aluminum alloy, lithium tin alloy, lithium germanium alloy, lithium gallium alloy, lithium indium alloy, lithium antimony alloy, lithium indium alloy, lithium zinc alloy, lithium lead alloy, lithium bismuth alloy, lithium gold alloy, and lithium silver alloy.

[0077] In this example, the lithium alloy may be used as part of the protective layer, for example, forming the alloy layer 30. The metal in the alloy layer 30 forms a stable covalent bond with the acidic polymer.

[0078] Alternatively, a lithium alloy may be used as the negative electrode active material, namely, the active material layer 20. The active material layer 20 can be firmly bonded to the protective layer.

[0079] In one example, the silicon-containing electrode material includes at least one of silicon element, silicon monoxide, a silicon-carbon composite material, and a silicon-iron composite material.

[0080] The above materials can all be used as negative electrode active materials and are firmly combined with the protective layer.

[0081] According to a second embodiment of the present application, a method for preparing the above-mentioned electrode is provided. The preparation method comprises:

[0082] The slurry containing the polymer and the alloy is applied to one side of the active material layer 20 and dried to obtain the electrode.

[0083] The polymer includes an acidic polymer, and the alloy includes a lithium alloy. The acidic polymer, the lithium alloy and the active material layer are as described above. The process of the method is simple, and a protective layer can be formed on one side of the active material layer 20. The structure of the electrode formed by the method is stable.

[0084] In one example, after drying the slurry, the step includes:

[0085] The active material layer 20 covered with the protective layer is assembled into a battery, and the battery is charged and discharged.

[0086] In this example, during the charging or discharging process, the lithium ion current 42 can pass through the polymer layer 40. The lithium ions in the lithium ion current 42 gain electrons and are reduced to lithium metal and deposited. The metal in the metal carbonate gains electrons and is reduced to metal, which forms a graft with the acidic polymer, namely the metal graft polymer 41. During the lithium ion deposition process, the lithium ions and lithium metal will react with the metal in the metal graft polymer 41 to form an alloy. Finally, a lithium alloy is formed. Since the lithium metal is concentrated on the surface of the active material layer 20, the alloy layer 30 is formed on the surface of the active material layer 20. For example, the alloy layer 30 is located between the polymer layer 40 and the active material layer 20.

[0087] In one example, the lithium alloy of the protective layer is obtained by reacting at least a metal carbonate and an organic lithium salt.

[0088] In this example, during the formation and capacity separation process, the battery is charged and discharged. During the charging or discharging process, the organic lithium salt forms a lithium ion current 42. The lithium ion current 42 can pass through the polymer layer 40. The lithium ions in the lithium ion current 42 gain electrons and are reduced to lithium metal and deposited. The metal in the metal carbonate gains electrons and is reduced to a metal, which is covalently bonded to the acidic polymer, i.e., the metal grafted polymer 41. During the lithium ion deposition process, the lithium ions and lithium metals will react with the metal in the metal grafted polymer 41 to alloy. Finally, a lithium alloy is formed. Since the lithium metal is concentrated on the surface of the active material layer 20, the alloy layer 30 is formed on the surface of the active material layer 20. For example, the alloy layer 30 is located between the polymer layer 40 and the active material layer 20.

[0089] In one example, the metal carbonate includes at least one of gold carbonate, silver carbonate, magnesium carbonate, tin carbonate, and zinc carbonate.

[0090] In this example, the metal carbonate can be reduced to form a metal during the formation and volume separation process. The metal can reduce the deposition overpotential of lithium ions, making the formation of lithium alloys easier and reducing the polarization of the battery. For example, the carbonate can form lithium-silver alloys, lithium-gold alloys, lithium-magnesium alloys, lithium-tin alloys, and lithium-zinc alloys.

[0091] In one example, the organic lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium hexafluorophosphate.

[0092] Lithium bis(trifluoromethanesulfonyl)imide is LITFSI; lithium bis(trifluoromethanesulfonyl)imide is LiFSI; lithium hexafluorophosphate is LiPF6. The above organic lithium salts can significantly improve the conductivity of the electrode, thereby making it easier to form the alloy layer 30.

[0093] In one example, the method of preparing the slurry includes:

[0094] S1, mixing a polymer, a metal carbonate and an organic solvent to obtain a first solution;

[0095] S2, drying the first solution to obtain a solid;

[0096] S3, dissolving the solid matter into the solution containing the organic lithium salt to obtain the slurry.

[0097] Specifically, in step S1, the acidic polymer is dissolved in an organic solvent. The metal carbonate is dissolved in the organic solvent under stirring so that the acidic polymer and the metal carbonate can be fully dissolved to obtain a first solution. The stirring can be performed by magnetic stirring, ultrasonic dispersion, etc. After being fully dispersed, in step S2, the first solution is placed in an oven for drying to obtain a solid.

[0098] In step S3, first, an organic lithium salt is dissolved in a solution, for example, an organic solution. Then, a solid is dissolved in a solution containing an organic lithium salt and stirred sufficiently to obtain a slurry. The slurry contains an acidic polymer, a metal carbonate and an organic lithium salt. The slurry can be applied to the surface of the active material layer 20. After drying, the solvent in the slurry evaporates to form an electrode.

[0099] The protective layer formed by the preparation method has uniform texture and thickness, and can protect the active material layer 20 .

[0100] In one example, the organic solvent includes at least one of tetrahydrofuran, N,N'-dimethylformamide, N,N'-dimethylacetamide, dioxane, ethanol, toluene, and xylene.

[0101] In this example, the organic solvent can effectively dissolve the acidic polymer and the metal carbonate and is easily volatilized during the drying process, which makes the preparation of the solid matter easy.

[0102] In one example, the organic solvent further includes at least one of hydrochloric acid, sulfuric acid, trifluoroacetic acid, acetic acid, phosphoric acid, methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, oxalic acid, and succinic acid.

[0103] In this example, the acid is capable of reacting with the metal carbonate to facilitate dissolution of the metal carbonate, and the acid does not react with the acidic polymer.

[0104] In one example, the solution containing the organic lithium salt contains acetonitrile.

[0105] In this example, the organic lithium salt is easily dissolved in acetonitrile due to the polarity of its anion part, thereby improving the solubility of the organic lithium salt, and acetonitrile does not chemically react with the organic lithium salt.

[0106] In one example, the mass ratio of the acidic polymer, the organic lithium salt and acetonitrile is (0.5-1.5):(0.6-0.9):(0.5-1.5).

[0107] In this example, within the above range, the acidic polymer and the organic lithium salt can be rapidly dissolved in acetonitrile, and the conductivity of the formed electrode is high.

[0108] Optionally, the mass ratio of the acidic polymer, the organic lithium salt and the acetonitrile is 0.6:0.6:0.5, 0.7:0.7:0.7, 0.6:0.7:0.8, 0.8:0.6:0.7, 0.6:0.8:0.9, 1:0.8:0.1, 1.1:0.7:1.2, 1.2:0.9:1.2, 1.3:0.8:1.4, 1.5:0.7:1.5, etc. The above ratio makes the electrode highly conductive.

[0109] Preferably, the mass ratio of the acidic polymer, the organic lithium salt and acetonitrile is 1:0.72:1. This ratio enables the acidic polymer and the organic lithium salt to be rapidly dissolved in acetonitrile.

[0110] According to a third embodiment of the present application, a battery is provided, which includes the electrode described in the present application or an electrode prepared by the method for preparing the electrode described in the present application.

[0111] The battery has the characteristics of excellent safety performance and long service life.

[0112] According to a fourth embodiment of the present application, an electric device is provided, which includes the battery described in the present application.

[0113] The electrical equipment may be, but is not limited to, a car, a computer, a mobile phone, a watch, etc. The electrical equipment has the characteristics of excellent safety performance and good durability.

[0114] Example:

[0115] S1, dissolving an acidic polymer in a solvent and adding a metal carbonate to form a first solution. In this step, the chemical formula of the acidic polymer is:

[0116]

[0117] The metal carbonate is magnesium carbonate. Take 20 g of the acidic polymer, add it to 200 mL of tetrahydrofuran solution containing 0.1 mol of hydrochloric acid, stir it under magnetic stirring for 1 hour, and then add 0.1 g of magnesium carbonate.

[0118] S2, drying the first solution to obtain a solid. In this step, the first solution is placed in an oven for drying for 12 hours to obtain a solid.

[0119] S3, dissolving the solid matter into a solution containing an organic lithium salt to obtain a slurry. In this step, the solid matter is dissolved in an acetonitrile solution of bistrifluoromethylsulfonyl imide lithium salt, wherein the mass ratio of the acidic polymer, the organic lithium salt and the acetonitrile is 1:0.72:1. Filter out the insoluble matter to obtain a slurry. Apply the slurry to lithium metal. Lithium metal is the negative electrode active material.

[0120] S4, drying the slurry. In this step, lithium metal is placed on a current collector 10, such as a negative electrode current collector, and the slurry is dried to obtain a negative electrode sheet. Figure 1 shown.

[0121] Next, the negative electrode sheet, the separator and the positive electrode sheet are assembled together to form a battery. The positive electrode sheet is a copper current collector. The separator is a PE separator. The electrolyte includes DOL and DME. The volume ratio of DOL and DME is 1:1; the concentration of LiTFSI in the electrolyte is 1 mol / L; the additive of the electrolyte is lithium nitrate, with a mass percentage of 1%.

[0122] Performance Test:

[0123] Formation and capacity distribution: First, the lithium in the negative electrode is heated at 1 mA / cm 2 The current density is deposited on the surface of the positive electrode. The deposition amount is 5mAh / cm 2 Then, at 1 mA / cm 2 The current density is high enough to remove all the lithium on the surface of the positive electrode and deposit it back on the negative electrode.

[0124] Cyclic charge and discharge: First, at 1 mA / cm 2 The current density is 5 mAh / cm2, which deposits lithium from the negative electrode onto the surface of the positive electrode. 2 ; Then, at 1 mA / cm 2 The current density is 1 mAh / cm 2 The amount of lithium is repeatedly removed / deposited 10 times, and after the cycle, all the lithium on the surface of the positive electrode is removed and deposited on the negative electrode. The average deposition overpotential of multiple cycles is recorded, and the coulomb efficiency of lithium is calculated. The formula for calculating the coulomb efficiency is:

[0125] Coulomb efficiency: lithium extraction amount / lithium deposition amount*100%

[0126] Comparative Example 1:

[0127] The positive electrode sheet is a copper current collector, the negative electrode sheet is a lithium metal sheet, and the diaphragm is a PE diaphragm. The electrolyte is the same as that in the embodiment. The positive electrode sheet, the negative electrode sheet and the diaphragm form a battery.

[0128] The testing method is the same as that of the embodiment.

[0129] Comparative Example 2:

[0130] The positive electrode sheet includes a copper current collector and a polymer protective layer. The material of the polymer protective layer is polyethylene oxide, namely PEO. The coating amount of PEO on the copper current collector is 1g / m 2 The negative electrode sheet is a lithium metal sheet. The diaphragm is a PE diaphragm. The electrolyte is the same as that in the embodiment. The positive electrode sheet, the negative electrode sheet and the diaphragm constitute a battery.

[0131] The testing method is the same as that of the embodiment.

[0132] The test results of the embodiment and comparative example 1 and comparative example 2 are shown in Table 1 and Figure 3 .in, Figure 3 The horizontal axis is time, unit: s; the vertical axis is voltage, unit: V. Figure 3 The curves include the curve of lithium deposition on the positive electrode and the curve of lithium deposition on the negative electrode. Figure 3 The platform voltage of lithium deposition onto the positive electrode can be used to obtain the deposition overpotential of the battery.

[0133] Table 1 - Comparison of deposition overpotential and coulombic efficiency of the embodiment and comparative examples 1 and 2

[0134] Deposition overpotential Lithium extraction capacity (mAh) Lithium deposition capacity (mAh) Coulomb efficiency Example 0.025V 14.79 15 98.6% Comparative Example 1 0.050V 13.56 15 90.4% Comparative Example 2 0.040V 14.30 15 95.3%

[0135] As can be seen from Table 1, the deposition overpotential of the battery of the embodiment is less than the deposition overpotential of the batteries of Comparative Example 1 and Comparative Example 2. The coulombic efficiency of the battery of the embodiment is higher than the coulombic efficiency of the batteries of the Comparative Example and Comparative Example 2. This indicates that the battery of the embodiment of the present application has the smallest energy loss and the smallest lithium loss during the charge and discharge process.

[0136] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.

[0137] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.

Claims

1. An electrode, characterized in that: include: an active material layer; A protective layer, the protective layer is located on one side of the active material layer, and the protective layer comprises a polymer and an alloy; The alloy comprises a lithium alloy; The polymer includes an acidic polymer.

2. The electrode according to claim 1, characterized in that The acidic polymer includes at least one of compound 1 and compound 2, and the general formulas of compound 1 and compound 2 are respectively: wherein R1 is -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2(CHCH3)CH2-, -PhCH2CH2-, -PhCH2CH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2CH2-, -CH2COCH2-, -CH2OCH2-, -CH2CH2OCH2-, -CH2CH2OCH2CH2-, or -CH2CH2OCH2CH2OCH2CH2-; R2 is -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2(CHCH3)CH2-, -PhCH2CH2-, -PhCH2CH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2-, -PhCOCH2CH2CH2-, -CH2COCH2-, -CH2OCH2-, -CH2CH2OCH2-, -CH2CH2OCH2CH2-, or -CH2CH2OCH2CH2OCH2CH2-; X1 is -COOH, -(CH2) d COOH, -SO3H, -(CH2) d SO3H or -CF3COOH, d is a natural number; X2 is -NHCOCF3, -NHSO2CF3 or -CF3SO2NHSO2CF3; m and n are both natural numbers, n / (m+n)=0.01-0.99, m / (m+n)=0.01-0.99; a and b are both natural numbers, a / (a+b)=0.01-0.99, b / (a+b)=0.01-0.

99.

3. The electrode according to claim 1, characterized in that The metal in the alloy is covalently bonded to the acidic polymer.

4. The electrode according to claim 1, characterized in that The active material layer includes at least one of lithium metal, lithium alloy, and silicon-containing electrode material.

5. The electrode according to claim 1 or 4, characterized in that: The lithium alloy includes at least one of lithium boron alloy, lithium magnesium alloy, lithium aluminum alloy, lithium tin alloy, lithium germanium alloy, lithium gallium alloy, lithium indium alloy, lithium antimony alloy, lithium indium alloy, lithium zinc alloy, lithium lead alloy, lithium bismuth alloy, lithium gold alloy and lithium silver alloy.

6. The electrode according to claim 4, characterized in that The silicon-containing electrode material includes at least one of silicon element, silicon monoxide, a silicon-carbon composite material, and a silicon-iron composite material.

7. A method for preparing an electrode according to any one of claims 1 to 6, characterized in that: include: The slurry containing the polymer and the alloy is applied to one side of the active material layer and dried to obtain the electrode.

8. The method for preparing an electrode according to claim 7, characterized in that: The lithium alloy is obtained by reacting at least a metal carbonate and an organic lithium salt.

9. The method for preparing an electrode according to claim 8, characterized in that: The metal carbonate includes at least one of gold carbonate, silver carbonate, magnesium carbonate, tin carbonate and zinc carbonate.

10. The method for preparing an electrode according to claim 8, characterized in that: The organic lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide and lithium hexafluorophosphate.

11. The method for preparing an electrode according to claim 8, characterized in that: The method for preparing the slurry comprises: Mixing the polymer, metal carbonate and organic solvent to obtain a first solution; Drying the first solution to obtain a solid; The solid matter is dissolved in a solution containing the organic lithium salt to obtain the slurry.

12. The method for preparing an electrode according to claim 11, characterized in that: The organic solvent includes at least one of tetrahydrofuran, N,N'-dimethylformamide, N,N'-dimethylacetamide, dioxane, ethanol, toluene and xylene.

13. The method for preparing an electrode according to claim 12, characterized in that: The organic solvent further includes at least one of hydrochloric acid, sulfuric acid, trifluoroacetic acid, acetic acid, phosphoric acid, methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, oxalic acid, and succinic acid.

14. The method for preparing an electrode according to claim 11, characterized in that: The solution containing the organic lithium salt contains acetonitrile.

15. The method for preparing an electrode according to claim 14, characterized in that: The mass ratio of the polymer, the organic lithium salt and the acetonitrile is (0.5-1.5):(0.6-0.9):(0.5-1.5).

16. A battery, characterized in that: An electrode comprising the electrode according to any one of claims 1 to 6 or an electrode prepared by the method for preparing an electrode according to any one of claims 7 to 15.

17. An electrical device comprising the battery according to claim 16.